2021
DOI: 10.3389/fcell.2021.745859
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking on the Immune Microenvironment and Immunogenicity and Its Relationship With the Prognosis of Immune Checkpoint Inhibitors in Non-small Cell Lung Cancer

Abstract: Background: The emergence of immune checkpoint inhibitors (ICIs) has opened a new chapter for the treatment of non-small cell lung cancer (NSCLC), and the best beneficiaries of ICI treatment are still being explored. Smoking status has been repeatedly confirmed to affect the efficacy of ICIs in NSCLC patients, but the specific mechanism is still unclear.Methods: We performed analysis on the Memorial Sloan Kettering Cancer Center (MSKCC) clinical NSCLC cohort receiving ICI treatment, The Cancer Genome Atlas (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…On the other hand, non-smokers seemed to display a more immunosuppressed state, with a higher infiltration of M2 pro-tumor macrophages. Our findings are in agreement with a recent study that showed that NSCLC patients who are previous or current smokers had a higher TMB and neoantigen load, accompanied by a higher infiltration of immune cells, compared to those classified as never-smokers [ 70 ]. However, unlike previous studies similar to ours, using statistical models like Random Forest and Multiple Linear Regression, we report for the first time that these results are not affected by, and are not a sole artifact of, other confounding factors; at least for the dataset that we analyze in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, non-smokers seemed to display a more immunosuppressed state, with a higher infiltration of M2 pro-tumor macrophages. Our findings are in agreement with a recent study that showed that NSCLC patients who are previous or current smokers had a higher TMB and neoantigen load, accompanied by a higher infiltration of immune cells, compared to those classified as never-smokers [ 70 ]. However, unlike previous studies similar to ours, using statistical models like Random Forest and Multiple Linear Regression, we report for the first time that these results are not affected by, and are not a sole artifact of, other confounding factors; at least for the dataset that we analyze in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…However, unlike previous studies similar to ours, using statistical models like Random Forest and Multiple Linear Regression, we report for the first time that these results are not affected by, and are not a sole artifact of, other confounding factors; at least for the dataset that we analyze in the present study. Moreover, in accordance with our results, they also reported following mass cytometry (CyTOF) analysis of fresh NSCLC tissues, that smokers have a more immune-activated TME, while the TME of non-smokers is in an immunosuppressed or resting state [ 70 ]. Our findings further suggest a more complex relationship between smoking status and immune infiltration.…”
Section: Discussionsupporting
confidence: 90%
“…Cigarette smoking was found to impact both innate and adaptive immunity and affect gut microbiota composition [120,121]. Furthermore, several studies on NSCLC patients demonstrated improved clinical outcomes to the ICI therapy in smokers versus non-smokers, suggesting that smoking may contribute to higher immunogenicity and activation of the immune microenvironment [122,123]. To our knowledge, a similar analysis investigating the impact of smoking on ICI efficacy in melanoma patients has not been performed yet.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the immune microenvironment of tumor from the non-smoking group is enriched for immunosuppressive related cells, including regulatory T cells and M2 macrophages. Finally, the non-smoking group also contained higher fractions of CD45RAhigh CD4+ T cells and CD45RAhigh CD8+ T cells, typically characteristic of naïve T cell subpopulations ( 54 ).…”
Section: Immune Landscape In Never-smoker Lung Cancer Patientsmentioning
confidence: 99%